Development of a prototype mobile application for monitoring patients with COVID-19 treated by Primary Health Care (Research, Society and Development, 2022)
In order to contain the transmissibility of COVID-19, this article presents the development of an application (APP) with mobile health (mhealth) technology to be used during the triage process of patients with clinical signs suggestive of COVID-19 in Primary Health Care (PHC). This is an applied type of research with a focus on technological production. First, a bibliographic research was carried out with an exploratory approach and later, after identifying the problem in the literature, meetings were held with a team of IT professionals to improve the technological development of the product, which started on 05/19/21 and ended in 05/04/22. The bibliographic research revealed that information technology (IT) tools were used to promote educational actions in the context of the contingency of COVID-19, while the APP proposed in this article has as its main novelty the survey of requirements for early identification and the clinical management of new cases of COVID-19 as well as the proposition of measures that permeate professional practice in PHC. The APP prototype life cycle was structured in five phases, namely: definition of requirements; planning; production of screens and functionalities; functional and environmental tests; commissioning, operation and maintenance. As a result, the article presents the APP development process through the phases of its life cycle. Thus, the APP will provide the opportunity for remote care, ensuring that the patient is treated safely for everyone, and will also allow for case management at the first level of care, avoid unnecessary referrals to other health services, in addition to stimulating their computerization. of the Unified Health System.